Preschoolers are sensitive to free riding in a public goods game - Vogelsang, Martina; Jensen, Keith; Kirschner, Sebastian; Tennie, Claudio; Tomasello, Michael (Frontiers in Psychology, 2014)
Despite the benefits of cooperation, selfish individuals often produce outcomes where everyone is worse off. This “tragedy of the commons” has been demonstrated experimentally in adults with the public goods game. Contributions to a public good decline over time due to free-riders who keep their endowments. Little is known about how children behave when confronted with this social dilemma. Forty-eight five-year-olds were tested using a novel nonverbal procedure and simplified choices more appropriate to their age than standard economic approaches. The rate of cooperation was initially very low and rose in the second round for the girls only. Children were affected by their previous outcome, as they free rode more after experiencing a lower outcome compared to the other group members.